IMPLEMENTASI KEBIJAKAN BAGIAN HUBUNGAN MASYARAKAT SEKRETARIAT DPRD DALAM MENINGKATKAN PUBLIKASI KEGIATAN DPRD KABUPATEN KAUR - Oksuntri, Roni (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
The activities of the DPRD public relations and secretariat section to increase the publication of Kaur Regency DPRD activities are carried out to cover and publish activities carried out by DPRD leaders and members to be conveyed to the public so that the public can know about the activities carried out by DPRD members for the 2019-2024 term as bearers of the legislative mandate. that society has given. There are many problems that occur in the implementation of coverage and publication of the activities of the leaders and members of the Kaur Regency DPRD, including poor internet signal, frequent power outages, journalistic staff in the public relations department and protocols that do not exist, and the attitude of the people in Kaur Regency that does not follow activities carried out by the people's representatives. The aim of this research is to describe and understand the implementation of policies in the public relations section of the DPRD secretariat to increase the publication of Kaur Regency DPRD activities which will be studied using George C. Edward III's theory. The research method uses a qualitative research approach. Data collection was carried out by interviews, observation, documentation studies and triangulation. The conclusion of this research is that the implementation of policies by the public relations section of the DPRD secretariat to increase the publication of Kaur Regency DPRD activities which are studied using Edward III's theory is quite good.